Hokuriku-plus familial hypercholesterolaemia registry study: rationale and study design. Issue 9 (10th September 2020) - Tada, Hayato; Okada, Hirofumi; Yoshida, Shohei; Shimojima, Masaya; Nomura, Akihiro; Tsuda, Toyonobu; Mori, Mika; Takashima, Shin-ichiro; Kato, Takeshi; Usui, Soichiro; Sakata, Kenji; Hayashi, Kenshi; et al.
Abstract : Introduction: Familial hypercholesterolaemia (FH) is an autosomal-dominant inherited genetic disease. It carries an extremely high cardiovascular risk associated with significantly elevated low-density lipoprotein (LDL) cholesterol. The diagnostic rate of this disease in some European nations is quite high, due to the presence of multiple prospective registries. On the other hand, few data—and in particular multicentre data—exist regarding this issue among Japanese subjects. Therefore, this study intends to assemble a multicentre registry that aims to comprehensively assess cardiovascular risk among Japanese FH patients while taking into account their genetic backgrounds. Methods and analysis: The Hokuriku-plus FH registry is a prospective, observational, multicentre cohort study, enrolling consecutive FH patients who fulfil the clinical criteria of FH in Japan from 37 participating hospitals mostly in Hokuriku region of Japan from April 2020 to March 2024. A total of 1000 patients will be enrolled into the study, and we plan to follow-up participants over 5 years. We will collect clinical parameters, including lipids, physical findings, genetic backgrounds and clinical events covering atherosclerotic and other important events, such as malignancies. The primary endpoint of this study is new atherosclerotic cardiovascular disease (ASCVD) events. The secondary endpoints are as follows: LDL cholesterol, secondary ASCVD events and the occurrence of other diseases including hypertension, diabetes and malignancies. Ethics and dissemination: This study is being conducted in compliance with the Declaration of Helsinki, the Ethical Guidelines for Medical and Health Research Involving Human Subjects, and all other applicable laws and guidelines in Japan. This study protocol has been approved by the Institutional Review Board at Kanazawa University. We will disseminate the final results at international conferences and in a peer-reviewed journal. Trial registration number: UMIN000038210.